Design and validation of a novel 3D-printed glenohumeral fusion prosthesis for the reconstruction of proximal humerus bone defects: a biomechanical study - Lin, Jiaming; Song, Guohui; Huang, Anfei; Hu, Jinxin; Tang, Qinglian; Lu, Jinchang; Huang, Yufeng; Gong, Ming; Zhu, Xiaojun; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2024)
All available methods for reconstruction after proximal humerus tumor resection have disadvantages, and the optimal reconstruction method remains uncertain. This study aimed to design a novel 3Dprinted glenohumeral fusion prosthesis and verify its feasibility and safety using biomechanical methods. Methods: We verified the feasibility and safety of the 3D-printed glenohumeral fusion prosthesis by finite element analysis and biomechanical experimentation. In the finite element analysis, three reconstruction methods were used, and displacement and von Mises stress were observed; on this basis, in the biomechanical experiment, models constructed with sawbones were classified into two groups. The force-displacement curve of the 3D-printed prosthesis was evaluated. Results: In terms of displacement, the finite element analysis showed greater overall stability for the novel prosthesis than traditional glenohumeral joint arthrodesis. There was no obvious stress concentration in the internal part of the 3D-printed glenohumeral fusion prosthesis; the stable structure bore most of the stress, and the force was well distributed. Adding lateral plate fixation improved the stability and mechanical properties of the prosthesis. Furthermore, the biomechanical results showed that without lateral plate fixation, the total displacement of the prosthesis doubled; adding lateral plate fixation could reduce and disperse strain on the glenoid.The design of the 3D-printed glenohumeral fusion prosthesis was rational, and its stability and mechanical properties were better than those of traditional glenohumeral joint arthrodesis. Biomechanical verification demonstrated the feasibility and safety of this prosthesis, indicating its potential for proximal humerus bone defect reconstruction after tumor resection.